# |
ODE |
Mathematica |
Maple |
\[
{}x {y^{\prime }}^{2}+\left (1-x^{2} y\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-\left (x^{2} y+3\right ) y^{\prime }+3 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-\left (x y+1\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-x^{2} y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} {y^{\prime }}^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+\left (x -y^{2}\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-x y \left (x +y\right ) y^{\prime }+x^{3} y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}\left (4 x -y\right ) {y^{\prime }}^{2}+6 \left (x -y\right ) y^{\prime }+2 x -5 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right )^{2} {y^{\prime }}^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x y^{2}-1\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right )^{2} {y^{\prime }}^{2} = 4 x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} {y^{\prime }}^{2}+\left (2 y^{2}+x y-x^{2}\right ) y^{\prime }+y \left (y-x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y \left (x^{2}+y^{2}\right ) \left ({y^{\prime }}^{2}-1\right ) = y^{\prime } \left (x^{4}+x^{2} y^{2}+y^{4}\right )
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{3}-\left (x^{2}+x +y\right ) {y^{\prime }}^{2}+\left (x^{2}+x y+y\right ) y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{4} {y^{\prime }}^{2}-x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+4 x^{5} y^{\prime }-12 x^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{3} {y^{\prime }}^{2}-4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{3} {y^{\prime }}^{2}+4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+x {y^{\prime }}^{2}-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{4} {y^{\prime }}^{3}-6 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+x^{3} y^{\prime }-2 x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+4 x^{5} y^{\prime }-12 x^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}2 x {y^{\prime }}^{3}-6 y {y^{\prime }}^{2}+x^{4} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+k {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x^{8} {y^{\prime }}^{2}+3 x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} {y^{\prime }}^{2}+2 x^{3} y y^{\prime }-4 = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{4} {y^{\prime }}^{2}-x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+\left (x -y\right ) y^{\prime }+1-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \left (x y^{\prime }-y+k \right )+a = 0
\] |
✓ |
✓ |
|
\[
{}x^{6} {y^{\prime }}^{3}-3 x y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y = x^{6} {y^{\prime }}^{3}-x y^{\prime }
\] |
✗ |
✓ |
|
\[
{}x {y^{\prime }}^{4}-2 y {y^{\prime }}^{3}+12 x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{3}-y {y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 {y^{\prime }}^{3}+x y^{\prime }-2 y = 0
\] |
✗ |
✓ |
|
\[
{}2 {y^{\prime }}^{2}+x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+2 x y^{\prime }-y = 0
\] |
✗ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2}-3 y y^{\prime }+3 = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}5 {y^{\prime }}^{2}+6 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x {y^{\prime }}^{2}+\left (2 x -y\right ) y^{\prime }+1-y = 0
\] |
✓ |
✓ |
|
\[
{}5 {y^{\prime }}^{2}+3 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+3 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+x^{3} {y^{\prime }}^{2}
\] |
✓ |
✗ |
|
\[
{}x^{3} {y^{\prime }}^{2}+x^{2} y y^{\prime }+4 = 0
\] |
✓ |
✓ |
|
\[
{}6 x {y^{\prime }}^{2}-\left (2 y+3 x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}9 {y^{\prime }}^{2}+3 y^{4} y^{\prime } x +y^{5} = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{3} {y^{\prime }}^{2}-4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{6} {y^{\prime }}^{2}-2 x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}5 {y^{\prime }}^{2}+6 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-y \left (1+x \right ) y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{5} {y^{\prime }}^{2}+12 x^{4} y y^{\prime }+9 = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{2} {y^{\prime }}^{3}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{4}+x y^{\prime }-3 y = 0
\] |
✗ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{3}-2 x y {y^{\prime }}^{2}+y^{\prime } y^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}16 x {y^{\prime }}^{2}+8 y y^{\prime }+y^{6} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-\left (x^{2}+1\right ) y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-2 x y^{\prime }-y = 0
\] |
✗ |
✓ |
|
\[
{}9 x y^{4} {y^{\prime }}^{2}-3 y^{5} y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-\left (2 x y+1\right ) y^{\prime }+y^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{6} {y^{\prime }}^{2} = 16 y+8 x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2} = \left (x -y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (1+y^{\prime }\right )^{2} \left (-x y^{\prime }+y\right ) = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-{y^{\prime }}^{2}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+y \left (1-x \right ) y^{\prime }-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-\left (x +y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+\left (k -x -y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{3}-2 y {y^{\prime }}^{2}+4 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x \ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+y^{2} = -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x} = 5 x^{2}
\] |
✓ |
✓ |
|
\[
{}t x^{\prime }+2 x = 4 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x -y}{x +4 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x} = 6 y^{2} x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{2}+\cos \left (x \right )+\left (2 x y+\sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y-1+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\cos \left (y\right ) \sec \left (x \right )}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (\cos \left (y\right )+y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sec \left (x \right ) \left (\sin \left (y\right )+y\right )}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (5+\frac {\sec \left (x \right )}{x}\right ) \left (\sin \left (y\right )+y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+\frac {\sec \left (x \right )}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +\frac {\sec \left (x \right ) y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\ln \left (1+y^{2}\right )}{\ln \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-x y-1}{4 x^{3} y-2 x^{2}}
\] |
✓ |
✓ |
|
\[
{}\frac {{y^{\prime }}^{2}}{4}-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {\frac {1+y}{y^{2}}}
\] |
✓ |
✓ |
|